Human Mobility Patterns for Different Regions in Myanmar Based on CDRs Data - Kyaing Kyaing; KoKo Lwin; Yoshihide Sekimoto (IPTEK Journal of Proceedings Series, 2017)
Sustainable urban and transportation planning depends greatly on understanding human mobility patterns in urban area. Myanmar is one of the developing countries in ASEAN. It develops more rapidly as compare past years due to its international trade policy change and faces serious traffic problem in major cities. To solve these problem, human mobility pattern need to know for improvement. Therefore, this paper focuses to analyze different human mobility patterns for the different regions in Myanmar by using Call Detail Records (CDRs) Data. Such studies could be useful for creating transport model of mobility pattern. The numbers of trip generated are obtained by using CDRs over seven days period. CDRs of each region can be used to generate trip numbers of townships within certain time frame and time windows. In this study, average distance travelled, preferred days of long distance users and human mobility patterns at different times of weekdays and weekends in Yangon and Mandalay were analyzed. People living in Yangon area are generally more travelled than Mandalay on weekdays and weekends. The results indicated the similarities and differences in mobility patterns for both cities. This information is very useful for transport planning and future transportation developments.